Green-Synthesized Silver Nanoparticles Using Erythrina subumbrans Leaf Extract: Optimization and Antibacterial Activity - Maharini, Indri; Utami, Karen Putri; Rachmawati, Lilis; Fitrianingsih, Fitrianingsih; Pratiwi, Puspa Dwi (Sciences of Pharmacy, 2026)
The high prevalence of acne and increasing antibiotic resistance necessitate the development of sustainable antimicrobial agents. This study investigated the green synthesis of silver nanoparticles (AgNPs) using Erythrina subumbrans (Hassk.) Merr. leaf extract as a natural bioreductant and stabilizer. The primary objective was to optimize the synthesis process and evaluate the antibacterial efficacy of the resulting nanoparticles specifically against Propionibacterium acnes. Physicochemical and structural characterization were performed using spectroscopic and microscopic techniques to confirm the formation and stability of the nanoparticles. The results successfully demonstrated the synthesis of crystalline, nanoscale AgNPs with plant-derived functional groups facilitating their stabilization. Analytical data indicated a relatively uniform particle size distribution, spherical morphology, and favorable surface characteristics, suggesting high suitability for biomedical integration. Significantly, the synthesized AgNPs exhibited potent antibacterial activity against P. acnes. The underlying mechanism of action is attributed to the disruption of bacterial cell membranes, induction of intracellular reactive oxygen species, and subsequent interference with vital cellular functions. Utilizing E. subumbrans extract offers an eco-friendly, cost-effective, and sustainable alternative to conventional chemical synthesis, reducing the reliance on toxic reagents. These findings highlight the significant potential of plant-mediated AgNPs as innovative antimicrobial agents for dermatological applications. This research provides a robust foundation for the advancement of nanotechnology-based topical treatments. Consequently, further investigation into pharmaceutical formulation development, comprehensive safety assessments, and clinical efficacy trials is highly recommended to establish E. subumbrans-mediated silver nanoparticles as viable therapeutic solutions for managing acne and other skin-related infections in the future.